Implementation Of Sugeno Fuzzy Logic Method On Microcontroller Based On Tomato Sorter - Mhd Furqan; Rakhmat Kurniawan; Abdul Halim Hasugian; Siti Sumita Harahap (INFOKUM, 2021)
As it is well known that tomatoes have different qualities and colors of ripeness, it is very necessary for a farmer to sort the tomatoes because then the farmers can target the marketing of tomatoes among the market, supermarkets, etc. Sorting tomatoes manually requires good concentration so as not to cause sorting errors, but sometimes concentration can be reduced due to sitting too long, etc., so that sorting occurs at will without paying attention to the tomatoes and this can also take a long time. To overcome this problem is to offer the manufacture of a tomato fruit sorter automatically by applying the Sugeno fuzzy logic method, which is a cryptic method which means that a value can be between true and false. With this tool can overcome the problem of sorting tomatoes and can minimize time. This Sugeno fuzzy logic method is used and utilized in processing the value of tomatoes in the form of RGB values. The result of this research is a tool that is able to sort tomatoes according to conditions, namely ripe, half-ripe, and unripe.